(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The resources which store the information electronically and are accessed with the help of electronic systems and networks are called as electronic resources. The e resources are the collection of data in the form of E-Journals, E-Books, E-Databases, E-Reports, E-Thesis, E-Newspapers, Internet/Websites, CD Rom/DVDs and other portable databases. Objective of the present study is to examine the usage of electronic resources, frequency, purpose, user satisfaction and problem faced by the users using electronic resources in the faculties of Coimbatore district. The study aimed at finding their user of e-resources by the faculty members in the arts and science college libraries. 200 questions were distributed, out of which 150 were returned. The result of this survey are presented and discussed in this paper.